Pore Structure Regulation and Electrochemical Performance Characterization of Activated Carbon for Supercapacitors - Li, Shijie; Xing, Tao; Wang, Yilin; Lu, Pengwei; Kong, Weixue; Li, Shenao; Su, Xiaomin; Wei, Xinkuan (Frontiers in Energy Research, 2021)
In order to achieve the purpose of regulating the pore structure characteristics of activated carbon by adjusting the experimental parameters, the effects of carbonization temperature, carbonization time, pre-activation temperature, pre-activation time and impregnation time on the pore structure of sargassum-based activated carbon (SAC) are studied by orthogonal experiment. The gravimetric capacitance of SAC and the relationship between the gravimetric capacitance and specific surface area are also studied. The results show that the SACs prepared at all experimental conditions have developed pore structure and huge specific surface area, reaching 3,122 m2/g. The pore size of SAC is almost all within 6 nm, in which the micropores are mainly concentrated in 0.4–0.8 nm, the mesopores are mainly concentrated in 2–4 nm, and the number of micropores is significantly higher than that of mesopores. During the preparation of SAC, the effect of carbonization temperature on the specific surface area and specific pore volume of SAC is very significant. The effect of carbonization time on the specific surface area of SAC is significant, but the effect on specific pore volume can be ignored. The effects of pre-activation temperature, pre-activation time, and impregnation time on specific surface area and specific pore volume of SAC can be ignored. In addition, SACs show good gravimetric capacitance performance as electrode material for supercapacitors, which can significantly increase the capacitance of supercapacitors and thus broaden their applications. The gravimetric capacitance and specific surface area of SACs show a good linear relationship when the activated carbons have similar material properties and pore size distribution.